2021
DOI: 10.3390/pathogens10121588
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pregnant Women with Ivermectin during Mass Drug Distribution: Time to Investigate Its Safety and Potential Benefits

Abstract: To date, pregnant women are excluded from programmes delivering community-directed treatment of ivermectin (CDTI) for onchocerciasis and preventive chemotherapy of other helminthiases because of concerns over ivermectin safety during pregnancy. This systematic exclusion sustains an infection reservoir at the community level and deprives a vulnerable population from known benefits—there are indications that treating O. volvulus infected women may improve pregnancy outcomes and reduce the risk that their childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In a case-control study in Northern Uganda, preterm birth was found to be a risk factor for NS [49]. As preterm birth could be related to an O. volvulus infection of the pregnant mother [50], it was suggested that an O. volvulus infection of the mothers could cause a "parasitic tolerance" in their offspring. This tolerance can induce a higher load of O. volvulus microfilarial infection when the children are exposed to O. volvulus-infected blackflies than if the mothers were free of infection during pregnancy [51].…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study in Northern Uganda, preterm birth was found to be a risk factor for NS [49]. As preterm birth could be related to an O. volvulus infection of the pregnant mother [50], it was suggested that an O. volvulus infection of the mothers could cause a "parasitic tolerance" in their offspring. This tolerance can induce a higher load of O. volvulus microfilarial infection when the children are exposed to O. volvulus-infected blackflies than if the mothers were free of infection during pregnancy [51].…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study in northern Uganda, preterm birth was found to be a risk factor for NS [64]. As preterm birth could be related to an O. volvulus infection of the pregnant mother [65], it was suggested that an O. volvulus infection of the mothers could cause a "parasitic tolerance" in their offspring. This tolerance could induce a higher load of O. volvulus microfilarial infection after the children are exposed to O. volvulus-infected blackflies than if the mothers were free of infection during pregnancy [66].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%